Does Fair Coach Behavior Predict the Quality of Athlete Leadership Among Belgian Volleyball and Basketball Players: The Vital Role of Team Identification and Task Cohesion - De Backer, Maarten; Van Puyenbroeck, Stef; Fransen, Katrien; Reynders, Bart; Boen, Filip; Malisse, Florian; Vande Broek, Gert (Frontiers in Psychology, 2022)
A vast stream of empirical work has revealed that coach and athlete leadership are important determinants of sport teams’ functioning and performance (Cotteril, 2013). Although coaches have a direct impact on individual and team outcomes, they should also strive to stimulate athletes to take up leadership roles in a qualitative manner. Yet, the relation between coach leadership behaviour and the extent of high-quality athlete leadership within teams remains underexposed. Based on organizational justice theory (Greenberg, 1990) and the social identity approach (Haslam, 2004), the present research tested whether perceived justice of the coach positively predicts the quality of athlete leadership. Furthermore, we examined the mediating role of group dynamic processes (i.e., team identification and task cohesion) within this relation. Belgian volleyball (N = 161) and basketball players (N = 78) were asked to rate the justice of their coach, their team identification, the team’s task cohesion, and the athlete leadership quality in the team. Structural equation modeling indicated that coaches’ perceived justice positively predicted the quality of athletes’ leadership, and that this relation was mediated by team identification and task cohesion. These results suggest that fair coach behaviour does not only bridge the gap between leadership and followership (Haslam et al., 2004), it also has the potential to improve the quality of athletes’ leadership within sport teams. More specifically, findings suggest that coaches’ perceived justice cultivates optimal group dynamic processes characterised by high levels of team identification and task cohesion, which in turn encourages athletes to express high-quality leadership.